Comparison of X-band satellite link measurements with radar derived rain attenuation in the tropics - Badron, Khairayu; Ismail, Ahmad Fadzil; Asnawi, Ani Liza; Ismail, Madzlan; Salim, Hamid; Mustafa, Hafidzah (Science and Knowledge Research Society www.sandkrs, 2014)
The analyses concerning comparison between measured signals of RazakSAT’s Malaysian X-band satellite link and radar derived attenuation using an S-band meteorological radar is presented. Weather radars have been consistently used for investigating propagation phenomena which can affect satellite communication links since the year 1960. A weather radar return which is known as reflectivity can be used to estimate rainfall intensity, attenuation and depolarization caused by hydrometeors. RazakSAT's satellite link received power during clear sky and rainy conditions are compared to extract the rain attenuation values. The S-band radar horizontal polarization reflectivity information was used to calculate the likely rain attenuation along the same RazakSAT satellite propagation paths. The radar reflectivity values are first converted into rainfall rate using the established Z-R relation of Marshall-Palmer. Afterwards the slant path attenuation is determined using the specific rain attenuation formula and the rainfall rate values. It can be observed that the radar derived rain attenuation values are lower than the measured satellite link signals.